Cevap :
Merhaba
[tex] \frac{5}{6} - ( \frac{7}{12} - \frac{5}{24} ) \\ ( \frac{7}{12} - \frac{5}{24} ) = \frac{14}{24} - \frac{5}{24} = \frac{9}{24} \\ \frac{5}{6} - \frac{9}{24} = \frac{20}{24} - \frac{9}{24} = \frac{11}{24} [/tex]
- Cevap D seçeneği olmalıdır.
#S∞T
Merhaba❀
- [tex]\frac{7}{12} = \frac{14}{24}[/tex]
- [tex]\frac{14}{24} - \frac{5}{24} = \frac{9}{24}[/tex]
- [tex]\frac{5}{6} = \frac{20}{24}[/tex]
- [tex]\frac{20}{24} - \frac{9}{24} = \frac{11}{24}[/tex]
- Cevap D şıkkı olacak.
Başarılar☆